Natural history notes on Cyrtonota sericinus (Erichson, 1847) in Ecuador (Coleoptera: Chrysomelidae: Cassidinae: Mesomphaliini) - Cedeño-Loja, Pedro Emilio (2020)
The first natural history data is reported for the tortoise beetle, Cyrtonota serinus (Erichson, 1847) (Chrysomelidae: Cassidinae: Mesomphaliini). An Ipomoea sp. (Convolvulaceae) is recorded as the host plant. Larvae and adults feed on the leaves. Larvae retain an exuvio-fecal shield and are gregarious. Adults are sexually dimorphic and polymorphic in sizes and coloration.